A new species of genus Rhabdophrya (Ciliophora: Suctorea) from the west coast of India and comments on the genus taxonomy - Chatterjee, Tapas; Dovgal, Igor; Sautya, Sabyasachi (Zootaxa, 2022)
The article presents the description of a new species of the suctorian genus Rhabdophrya inhabiting the body surface (cuticle) of harpacticoid copepod from Navy-Nagar, Mumbai intertidal coralline region, west coast of India, the Arabian Sea. The diagnosis of the genus is refined, all other species diagnoses and identification keys are presented.